Monolithic pouring of the foundation slab of the 632‐m high Shanghai Tower. (10th May 2017) - Gong, Jian; Cui, Weijiu; Yuan, Yong
Abstract : To have an impermeable and integrate foundation, a slab requires the continuous pouring of concrete without any joint. However, it challenges the engineers in practice because the huge volume of fresh concrete should be prepared in a plant, be transported via buggy, and be pumped on site. Thermal cracking after massive concreting is another critical issue to be considered in advance. This paper presents the monolithic pouring of 60, 000 m 3 concrete for the foundation raft of the Shanghai Tower. Selection of raw materials was introduced in the orientation of hydration heat reduction. Trial pouring of a block verified the workability and feasibility of the proposed concrete matrix composition. To organize monolithic concreting, a huge slab installation of concrete pumps and the facilitation of placing chutes was introduced as well to achieve continuous pouring from the core region toward the outside ring. Temperature monitoring after monolithic placement of concrete indicated that the prediction with numerical simulation was successful in assisting construction organization.